ADAPTASI PEDAGANG PASAR IMOGIRI PASCA REVITALISASI PASAR TRADISIONAL DI BANTUL - , MARYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The market is a venue for economic activity. During, the economic activity takes place an interaction between traders, buyers, suppliers and the government. The focus this study was conducted the adaptation of Imogiri market traders after the revitalization of traditional markets. The selection of located in Bantul because the majority of the population works in the agriculture and the trade. The earthquake happening on 2006, resulted in the paralysis of economic activity because markets were damaged. Imogiri market was one of the damaged markets. The government took several to the revitalize of Imogiri market. This research borrows the theory of Merton. The forms of adaptation that Merton mentioned are conformity, innovative, ritualism, and retreatism. This study used the qualitative method with a case study approach. The selection of this method is because the process of the adaptation of the traders of the Imogiri market trader was different from others market which were relocated. The unit of analysis the study is trader. The data collection was done of participant observation, interviews and document searches. The results of the observations, interviews and tracking of documents that have to the analyzed and conclusions of drawn. The results showed that the revitalization of the Imogiri market has changed of the building. The change requires of the building market traders adjust to the new state of the physical environment. Such the adaptation is referred to as a physical the form of adaptation. The physical form of adaptation is done by traders in the Imogiri market. The variations of adaptation found in the Imogiri market traders are cooperation, increasing the merchandise, add variety the merchandise, move to peddle the merchandise and stay afloat. The trader not only adapt through one way. There were the traders who perform of adaptation used two or more ways. There were also the traders who do not adapted as their business has been developed.